Poaching upsurge in Garamba National Park, Democratic Republic of Congo - Smith, Hillman; Fraser Smith; Paulin Tshikaya; Jerome Ndey; John Watkin (Pachyderm)
'Since 1991 the threat to large mammals, generated largely by the side effects of the war in adjacent Sudan, has been gradually increasing and has moved down through the park towards the southern sector where the elephants and rhinos are found.' This article reviews the populations loss of buffalo, rhino and elephant in Garamba NP and adjacent reserves of Azande, Gangala na Bodio and Mondo Missa in northwestern DRC in three phases: 1991-1997, 1997-2003 and late June 2003 to the present (journal published in January 2004). In 1991 when some 80000 Sudanese refugees settled in the vicinity of Garamba meat from bufflalo became their major protein source. In 1993 the majority of the poaching still occurred in the north and central regions of the Park , but by 1997 during DRC's own civil war poaching had moved into the southern sector. The civil war precipitated poaching and certainly not only for meat. In 1997 alone it is considered that the elephant population was halved (11175 +/-3670 to 5874+/-1339). By 1999 the southern sector was the focus for poaching. 'Since June 2003 poaching in Garamba NP has changed from meat to ivory. The level of poaching of elephants has exploded '. In August an aerial survey noted 34 fresh elephant carcasses while a November survey observed 27 fresh and recent carcasses plus 7 additional old ones. Most of the poachers are well armed Sudanese military and military deserters. Guards trained and supported through the internationally funded Garamba National Park Project and its core expatriate staff focus on protecting the few remaining rhino and the elephant population in the southern sector.